Dental Trauma: A Practical Guide to Diagnosis and Management - Djemal, S. Serpil (Jaypee Brothers Medical Publishers, 2021)
The aim of this book is to focus on how to assess, diagnose and effectively manage traumatic dental injuries. Traumatic dental injuries occur for a variety of unfortunate reasons and can manifest in a number of ways. This book consists of 14 chapters, which include first principles, splinting, infractions and enamel fractures, enamel-dentine fractures, enamel-dentine-pulp fractures, crown-root fractures, root fractures, concussion and subluxation, extrusion, lateral luxation, intrusion, avulsion, dentoalveolar fractures, and long-term consequences of dental trauma. Each chapter summarizes how best to assess and manage the presenting problem and includes advice on postoperative care and recommended follow-up. A clinical case example highlighting salient points is featured for each topic, and more than 400 clinical photographs and explanatory diagrams throughout the book further enhance learning.